Faktor-Faktor Yang Mempengaruhi Saturasi Oksigen dan Lama Hari Rawat Pada Pasien PPOK yang Mendapatkan Posisi Semifowler di RS Hermina Ciputat: Faktor-Faktor Yang Mempengaruhi Saturasi Oksigen dan Lama Hari Rawat Pada Pasien PPOK yang Mendapatkan Posisi Semifowler di RS Hermina Ciputat - Desy Rasmiyani; Khodijah Alkaff; Surwaningsih; Mega Hasanul Huda; Muhammad Fauzi Rahman; Yuhendri Putra; Intan Asri Nurani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a lung disease which has a chronic obstruction in airway that can interefere normal respiration led to death. Patients with COPD usually show symptoms such as dyspnea that are most frustrating in patients with COPD that can trigger the appearance of tightness and decreased saturation. The semi-fowler position is a position that can be chosen by patients who have difficulty breathing and in COPD patients is expected to optimize lung development so that oxygen saturation becomes increased. Given the many factors that contribute to oxygen saturation in patients, it is important to control the factors that affect oxygen saturation in patients who get a semi-fowler position. In addition, given the high prevalence of COPD, it is important for hospitals to identify factors that affect the length of day of treatment of patients with COPD. Identification of these factors can help health workers to plan treatment programs to plan the length of the day of treatment of patients who enter the hospital. The study aimed to identify factors that influence oxygen saturation and the length of days of treatment in COPD patients who get semi-fowler positions at Hermina Ciputat Hospital. Data collection was carried out from January 2020 to October 2021 using the cross-sectional method, namely by taking data at once at the same time through medical record data on 84 inpatients. The analysis test used in this study is the T-test and subsequently multivariate analysis is carried out using linear regression tests. Based on the analysis test, the factors that affect oxygen saturation are gender, smoking history, and initial saturation value. While the factors that affect the length of treatment are the history of smokers and the history of comorbid. Respondents who had a history of smoking would experience a decrease in oxygen saturation by 0.3888. Preventive interventions through smoking-related health education need to be done to reduce the severity in patients with COPD who are hospitalized.